From status-seeking consumption to social norms: An application to the consumption of cleanliness - Julia Sophie Woersdorfer (Max Planck Institute of Economics, 2008)
Interdependencies in consumer behavior stem from either status-seeking consumption or compliance with social norms. This paper analyzes how a consumption act changes from a means to signal the consumer's status to a means of norm compliance. It is shown that such a transformation can only be understood when consumer motivations other than social recognition are taken into account. We depict norm emergence as a learning process based on changing associations between a specific consumption act and widely shared, non-subjectivist consumer needs. Our conjectures are illustrated by means of a case study: the emergence of the cleanliness norm in the 19th century.
Keywords: D02; D11; D62; D83; 330; social norms; status seeking; externalities; consumer needs; consumer learning; cleanliness